TECHNOLOGY INTEGRATION IN INDONESIAN EFL CLASSROOMS: PATTERNS, CONSIDERATIONS, AND IMPACTS - Annisa Nurul Lestari; Sofendi; Machdalena Vianty (University of Kuningan, 2026)
This study examines how educational technologies are integrated into English as a Foreign Language (EFL) teaching and learning at a public senior high school in Indonesia from both teacher and student perspectives. Data were collected through open-ended questionnaires from 306 students and semi-structured interviews with seven English teachers and analyzed using Braun and Clarke’s (2006) Thematic Analysis. The findings reveal that a wide range of technologies including hardware, communication tools, learning platforms, AI tools, online dictionaries, presentation tools, and social media support EFL learning. Teachers’ technology use is influenced by pedagogical clarity, practicality, device compatibility, and school-supported facilities, while students utilize digital tools to enhance comprehension, vocabulary, pronunciation, and assignment completion. Technology improves students’ motivation, engagement, and participation, but challenges such as unstable internet, limited devices, technical disruptions, and lack of dedicated multimedia spaces remain. Coping strategies include preparing backup materials, sharing devices, using school Wi-Fi, employing offline alternatives, and seeking peer or teacher support. Overall, technology positively contributes to learning effectiveness, but strengthening digital readiness and school infrastructure is essential to maximize its potential. This study uniquely triangulates teacher and student perspectives in a resource-constrained context, offering practical implications for EFL classrooms.